Modern ways of water resources management (Journal of Geography and Environmental Management, 2019)
River runoff, accumulating a total waste production process is very sensitive to human disturbance during the extensiveexploitation of natural resources, which severely appears on the general environmental condition of water resources.Conversion problems of river systems should be closely linked with the main objectives of environmental managementsolutions which provide rational use of water and land fund and protect the ecological balance in the basin.